Desain Sistem Pendukung Keputusan Seleksi Calon Guru Sekolah Alam Berbasis Islam - Hilyah Magdalena; Rani Rani (CogITo Smart Journal, 2018)
Sekolah Alam Bangka Belitung, which currently organizes educational activities at the elementary school level with Islamic concepts and is more learning outside the classroom, requires teachers or what is termed facilitator. The facilitator needed by the Sekolah Alam is a facilitator who meets multi criteria such as attitudes, academic, skills, abilities, interviews, and three-month internships. To get a facilitator that fits the criteria desired by the Sekolah Alam, this study designs a decision support system to select candidate facilitators using the Analytical Hierarchy Process (AHP) method. The AHP method is chosen to form a hierarchy of facilitator selection frameworks starting with objectives, level one criteria, level two criteria, and alternatives. After the decision-making scheme, then this research moves the decision-making pattern into a web-based information system built with the method of Object Oriented Analysis and Design (OOAD). Data processing results show that the highest level 1 criterion is the attitude with 34.1%, the second is a 3-month internship with a weight of 33.3%, the third is an academic with a weight of 13.4%, the fourth is a skill with a weight of 11.3 %, the last is an interview with a weight of 8%. While the web-based system design that is designed to make the decision-making process can be done more accurately, easily, and flexibly